Authenticating Neoliberalism: Korean Official Development Assistance in Uganda and the East African Region - Musasizi, Joseph; Watson, Iain (World review of political economy, 2024)
Neoliberalism—in the form of privatization, deregulation, and the creation of new spatial zones and legal arrangements of land ownership—is promoted by the state to ensure an investment climate for capital accumulation. Neoliberalism uniquely combines economic deregulation and state rollback with the rollout of state strategies that ensure surplus and rentier extraction. Foreign aid has typically been regarded as a means of ensuring economic growth and development provided by the donor state. Recently, there has been an interest in the role of the private sector in development studies. Korean foreign aid, based on the new village movement development model now being used in Uganda, represents a new phase of neoliberalism in Uganda and East Africa. The new village movement is a state-driven attempt to create new neoliberal subjects and identities to prepare for future neoliberal capital accumulation in a middle-income context. Aid-recipient states such as Uganda are using Korean official development assistance to legitimate a specific rollout of neoliberal state regulations. This marks a shift from the previous disciplinary neoliberalism to the preparation of selected populations as marketable neoliberal subjects under the guise of authentic culture, resilience, and productivity.